ATP release by cardiac myocytes in a simulated ischaemia model Inhibition by a connexin mimetic and enhancement by an antiarrhythmic peptide - CLARKE, Thomas C; WILLIAMS, Oliver J. S; MARTIN, Patricia E. M; EVANS, W. Howard (European journal of pharmacology, 2009)
We studied the role of connexin hemichannels in the release of ATP by neonatal cardiac myocytes subject to ischaemic stress. Mechanical, osmotic and oxidative stress and changes in extracellular or intracellular Ca(2+) levels induce connexin hemichannels located in the plasma membrane to open and release small ions and molecules with signaling potential such as ATP. Since ATP release has been implicated in adaptation to oxygen deprivation, we studied its release by cardiac myocytes incubated in a custom-built hypoxia chamber for various periods. In a simulated ischaemia model (0.5% oxygen and 0.2 g/l glucose) a peak of ATP release occurred at 80 min followed by a return to steady state levels for a further 200 min. This peak of ATP release was not observed in myocytes subject to hypoxia (0.5% oxygen, 3.0 g/l glucose). ATP release in ischaemia was influenced by two classes of reagents that target connexins, the channel forming proteins of gap junctions. First, the connexin hemichannel inhibitors Gap 26 and 18a glycyrrhetinic acid abolished the ATP peak of release. Second, the AAP10, a peptide with antiarrhythmic properties markedly increased the peak of ATP release observed at 80 min of ischaemia and also induced a second smaller peak at 180-240 min. ATP content of the myocytes and Cx43 phosphorylation were monitored. Since the release of ATP in ischaemia was abolished by connexin channel inhibitors and stimulated by a peptide developed to target connexins in the context of cardiac arrhythmia, the results suggest that nucleotide release by connexin hemichannels is likely to feature in the response of myocytes to ischaemic stress in the heart.